Acute lower limb ischemia: 7 years of thromboembolectomies in the elderly - Moreira,Mário (2018)
Introduction: Acute lower limb ischemia (ALLI) is a common emergency in Vascular Surgery, with significant morbidity and mortality. Despite other therapeutic options, thromboembolectomy is still a valid option. The aim of this study is to assess the safety and efficacy of this surgical option in the treatment of ALLI, in elderly patients. Methods: Retrospective, single center study covering the period between January 2010 and December 2016, including all patients at least 80 years old suffering with ALLI, treated by thromboembolectomy. Exclusion criteria were bilateral ALLI, previous revascularization procedures and additional revascularization procedures in the index event. Thirty day major amputation and mortality were the analyzed outcomes. Results: We identified 254 patients. Thirty day postoperative major amputation rate was 9.4% (n=24) and mortality rate was 5.9% (n=15). Predictors of 30-day major amputation include prolonged ischemia time and increased ischemia severity. Previous diagnosis of arrhythmia is associated with lower amputation risk. No association between the studied covariates and mortality were obtained. Discussion: Our study show ischemia time as leading factor determining limb salvage, emphasizing the importance of health professionals' awareness for this condition. Regarding perioperative mortality, we did not find significant association among studied covariates; this can be explained by small number of deaths, what can hinder statistical analyzes. Conclusion: Thromboembolectomy is a valid option in ALLI treatment, even for elderly patients with multiple comorbidities. The difference between arrhythmia prevalence and patients taking anticoagulants expose a possible weakness in the management of these patients.